1994
DOI: 10.1523/jneurosci.14-01-00075.1994
|View full text |Cite
|
Sign up to set email alerts
|

Death of developing septal cholinergic neurons following NGF withdrawal in vitro: protection by protein synthesis inhibition

Abstract: Fetal septal neurons were grown in vitro under glass coverslips. This sandwich culture method significantly increased general neuronal survival, reduced glial proliferation, and permitted the removal of serum from the growth medium after 5 d in vitro. Thereafter, a simple, and completely defined, medium was used, and the effects of NGF, NGF withdrawal, and protein synthesis inhibition were examined on septal cholinergic neurons. NGF added to septal cultures at the time of plating resulted in a threefold increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 35 publications
6
36
0
1
Order By: Relevance
“…Under these very different conditions, DHEA had a major attenuating effect on the neurotoxic action of NMDA. We used a standard concentration of NMDA in vitro (1 mM) that was slightly higher than that of some previous studies because the experiments were done on inverted cultures (15). Parallel experiments showed that, although DHEAS also protected neurons in vitro against NMDA, it seemed less potent because significant protection only was observed at Ϸ10 times the lowest effective dose of DHEA (10 nM) used in these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these very different conditions, DHEA had a major attenuating effect on the neurotoxic action of NMDA. We used a standard concentration of NMDA in vitro (1 mM) that was slightly higher than that of some previous studies because the experiments were done on inverted cultures (15). Parallel experiments showed that, although DHEAS also protected neurons in vitro against NMDA, it seemed less potent because significant protection only was observed at Ϸ10 times the lowest effective dose of DHEA (10 nM) used in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The wells were then flooded with culture medium, a total volume of 500 l of DMEM supplemented with B27 (1:50) growth medium (GIBCO͞BRL), streptomycin (25 g/ ml)/penicillin G sodium (10,000 g/ml)͞amphotericin B (0.85%) (Sigma), and 5% fetal calf serum (GIBCO͞BRL). The coverslips were inverted within 24 h to maximize neuronal survival (14,15). On day 5 (plating day is day 0), the cultures in the medium were changed, and the concentration of fetal calf serum was reduced to 1%.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of cholinergic neurons in BF cultures maintained under similar conditions is low (ϳ1%) (Hartikka and Hefti, 1988;Svendsen et al, 1994). However, their unique ability to synthesize ACh makes quantification of supernatant ACh a reliable measure of their neurotransmitter release.…”
Section: Methodsmentioning
confidence: 99%
“…Regions of BFCN innervation (e.g., hippocampus, cortex) are enriched in NGF (Korsching et al, 1985;Large et al, 1986), and NGF is retrogradely transported by BFCNs (DiStefano et al, 1992), with these neurons expressing TrkA and p75NTR receptors (Koh and Loy, 1989;Holtzman et al, 1992). NGF and TrkA are important for BFCN development, maintenance, and function in vivo (Vantini et al, 1989;Li et al, 1995;Chen et al, 1997;Fagan et al, 1997;Molnar et al, 1998;Debeir et al, 1999;Ruberti et al, 2000), and NGF exposure (days to weeks) enhances cholinergic markers in BF cultures (Hartikka and Hefti, 1988;Takei et al, 1988Takei et al, , 1989Svendsen et al, 1994;Nonner et al, 1996;Pongrac and Rylett, 1998;Oosawa et al, 1999;Auld et al, 2001). The neurotrophins brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and neurotrophin-4 (NT-4) also enhance cholinergic markers (Nonomura et al, 1995;Nonner et al, 1996;Auld et al, 2001).…”
Section: Abstract: Brain-derived Neurotrophic Factor; Choline Acetylmentioning
confidence: 99%
“…CytC was delivered as a control protein at the same concentration and flow rate. Concentrations of 0.1 ng͞l of NGF previously have been shown to stimulate the maturation of septal cholinergic neurons in vitro (36).…”
Section: Validation Of Microdialysis Probe Placement and Ngfmentioning
confidence: 99%